Hypomania Checklist‐32 – cross‐validation of shorter versions screening for bipolar disorders in an epidemiological study. (9th March 2017) - Meyer, T. D.; Castelao, E.; Gholamrezaee, M.; Angst, J.; Preisig, M.
Abstract : Objective: Self‐reports such as Hypomania Checklist (HCL‐32) can be used to enhance recognition of bipolar disorders, but they are often too long and only validated in clinical samples. The objectives of this study are therefore to test whether (i) the HCL‐32 can be used for screening in the community and (ii) whether two previously suggested shorter versions would do as well. Method: Data stemmed from the CoLaus|PsyColaus, a prospective cohort study which included randomly selected residents aged 35–66 years from an urban area. Participants underwent semistructured interviews to assess DSM‐IV disorders and 1712 of them completed the HCL‐32. Results: Forty individuals (2.3%) were diagnosed as having BD. Compared to others, participants with BD scored significantly higher on the HCL‐32. The HCL‐32 had a sensitivity of 0.78 and specificity of 0.68. Very similar figures were found for two previously proposed shorter versions with 16 and 20 items. The results of confirmatory factor analysis and item response theory (IRT) models supported the postulated two‐factor structure for the three HCL versions. Conclusion: Despite the low base rate of BD in this sample, the screening properties of the HCL‐32 remained almost as good. Importantly, two previously proposed shorter versions performed as well, suggesting that those could be used without losing essential information.